Families at leisure outdoors: well-being through adventure. Issue 4 (4th July 2019) - Pomfret, Gill; Varley, Peter
ABSTRACT: This study investigates families who choose to co-participate in outdoor adventure holidays, and explores how they benefit from these shared experiences. In so doing, it seeks to determine the role of adventure tourism in developing and enhancing family well-being (FWB). Hyper-modern family life for many is powered by technological hardware, each room in the house replete with on-line pleasures, distractions and identities. In response to this dystopia, some families opt to take adventure holidays together. However, scholarship concerning collective experiences of adventurous leisure, in this case as families, is limited. Using a qualitative whole family approach, 15 (adventure tourist) families were interviewed, totalling 62 interviewees (29 adults and 33 children under 18 years old), in their home environments. Four key themes related to FWB emerged. First, families extended their active lifestyles to adventure holidays and repeatedly mentioned the health and fitness benefits gained from these experiences. Second, adventure holidays facilitated unmediated time together for families. Third, parents harboured ideals of positive personal development for their children in these adventure settings. Fourth, making memories during adventure holidays, and recollecting these post-trip, were integral to family bonding. Further research should consider non-traditional families, and various socio-economic and cultural groups in this context.